Antibiotic prophylaxis may not be indicated for prevention of dental implant infections in healthy patients. A systematic review and meta-analysis (2020)
Objectives The purpose of the present systematic review and meta-analysis is to determine the efficacy of antibiotic prophylaxis and specific antibiotic regimens in dental implant placement for prevention of post-operative infection (POI) in overall healthy patients. Materials and methods Electronic database and manual searches were independently conducted to identify randomized controlled trials (RCTs). Publications were selected on basis of eligibility criteria and then assessed for risk-of-bias using the Cochrane Handbook. The primary outcome was POI (total, early, and late). Wound dehiscence, pain, and adverse events were studied as secondary outcomes. Random-effects meta-analysis was conducted for risk ratios of dichotomous data. This systematic review was conducted in accordance with Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Results With duplicates removed, 1022 abstracts were screened and 22 full-text articles assessed; 10 RCTs of 1934 total patients were included. Meta-analysis did not detect statistically significant differences in total (P = 0.82), early (1–2 week post-op) (P = 0.57), or late (3–4 months post-op) (P = 0.66) POIs, wound dehiscence (P = 0.31), and adverse events (P = 0.21), between antibiotic and no-antibiotic groups. Confounding variables identified. Conclusion The results of this systematic review suggest that antibiotic prophylaxis may not be indicated for prevention of POIs following dental implant placement in overall healthy patients. These findings and in light of antibiotic-associated risks for individual and public health demand revaluation of routine prescription of antibiotic prophylaxis in dental implant placement procedures. Clinical relevance It is up to the clinicians to evaluate the benefits (or lack thereof) of antibiotic prophylaxis for each patient given medical history and surgical complexity, until new evidence becomes available.